In situ hydrodynamic observations on three reef flats in the Nansha Islands, South China Sea - Li, Jin; Wang, Ya Ping; Gao, Shu (Frontiers in Marine Science, 2024)
Waves and currents are responsible for sediment movement around and off coral reefs, affecting reef growth at both geological and modern timescales. Given the wide distribution and limited hydrodynamic information of reefs in the South China Sea, we carried out observations on tidal-cycle hydrodynamics in the Nansha Islands with tripod stationary instruments on the seafloor in order to fill the gap in our understanding of these processes. It was found that the magnitudes of near-bed orbital velocity were comparable with that of the mean tidal current, despite generally calm wave conditions. Waves dominated the combined wave-current skin-friction shear velocities acting on reef sediment, which were significantly higher than those generated by currents alone. Due to the large physical roughness of reef, drag coefficient and hydrodynamic roughness length estimated from logarithmic velocity profiles were two orders of magnitude higher than that in macro-tidal-estuary or inner shelf areas covered with siliceous muds or sands. The combined sinusoidal wave and asymmetric tidal current, along with the physical reef roughness, shaped velocity profile structures in the bottom boundary layer, which exhibited a logarithmic profile during the flood tide and a potential flow during the ebb. In absence of wave breaking, strong turbulence dissipation was observed across the rough reef, promoting strong mixing of water, which is crucial for delivering nutrients for coral growth. These findings imply the need to consider the unique characteristics of rough reef structure and combined effects of waves and currents to model the hydrodynamics in reef environment correctly. This understanding is critical for predicting energy and material transport in reef environments, which is essential for maintaining healthy coral ecosystems, and opens new paths for managing and preserving coral reefs in the face of environmental change.